Performance Evaluation and Comparison of Default and Small Private Key Rainbow Digital Signature Scheme for IoT Devices - Dornelles, Matheus da F.; Lara, Pedro Carlos da S.; Henriques, Felipe da R. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2019: Proceedings of the 25th Brazilian Symposium on Multimedia and the Web, 2019)
With the advent of quantum computers, the security of cryptographic systems based on the problem of the discrete logarithm (PLD) will be compromised. The Internet of Things (IoT) security will be directly affected because it is largely dependent on theses cryptographic techniques. Systems of Multivariate Quadratic Equations (MQ) will become more relevant in cryptography due to the resistance against attacks from these computers. The Rainbow signature scheme is a well known post–quantum algorithm based on MQ. This paper presents a comparison between the default version of Rainbow with a modified one, applied to IoT devices.